Synthesis and Characterization of Lanthanide(III) Complexes of N,N´-Propylene-bis(3-carboxypropenamide) - Babu, N. (Asian Journal of Chemistry, 2016)
Ten complexes of lanthanides with a polydentate ligand N,N´-propylene-bis(3-carboxypropenamide) (PBCPH2) have been synthesized and characterized by elemental analysis, conductance, magnetic measurements, infrared spectral and thermal analysis. The thermal analysis of the complexes proves the presence of three molecules of coordinated water molecules in all. The complexes have been assigned the formula [Ln·L·X·3H2O] where Ln = lanthanide ions and L = [PBCP]2– and X = NO3– or NCS–. In these complexes, the ligand acts as tetradentate.